Risk factors and reconstruction techniques for persistent cerebrospinal fluid leak in patients undergoing endoscopic endonasal approach to the posterior fossa (2021)
Background High-flow skull base dural defects are associated with an increased risk of postoperative cerebrospinal fluid (CSF) leaks. Objective This study aimed to identify the risk factors for persistent postoperative CSF leak after endoscopic endonasal surgery (EES) and determine the ideal reconstruction strategy after initial failed repair. Methods Patients with CSF leak after intradural EES between October 2000 and February 2017 were identified. Cases with persistent CSF leak were compared with patients with similar pathologic diagnosis without a persistent leak to identify additional risk factors. Results Two hundred and twenty-three out of 3,232 patients developed postoperative CSF leak. Persistent leaks requiring more than one postoperative repair occurred in 7/223 patients (3.1%). All seven had undergone intradural approach to the posterior fossa for resection of recurrent/residual clival chordomas. This group was matched with 25 patients with recurrent/residual clival chordoma who underwent EES without postoperative CSF leak (control group). Age, gender, history of diabetes, smoking, or radiotherapy were not statistically different between the groups. Obesity (body mass index > 30) was significantly more common in the group with persistent leak (86%) compared with controls (36%) (p = 0.02). All patients with a persistent CSF leak developed meningitis (p = 0.001). Five patients with persistent leak required a pericranial flap to achieve definitive repair. Conclusion Multiple recurrent CSF leak after EES primarily occurs following resection of recurrent/residual posterior fossa chordoma. Obesity is a major risk factor and meningitis is universal with persistent leak. Flap necrosis may play a role in the development of persistent CSF leaks, and the use of secondary vascularized flaps, specifically extracranial-pericranial flaps, should be considered as an early rescue option in obese patients.